Analysis of Human Immunodeficiency Virus Matrix Domain Replacements - Scholz, Isabel (2007)
The matrix (MA) domain of the HIV-1 structural precursor Gag (PrGag) protein targets PrGag proteins to membrane assembly sites, and facilitates incorporation of envelope proteins into virions. To evaluate the specific requirements for the MA membrane-binding domain (MBD) in HIV-1 assembly and replication, we examined viruses in which MA was replaced by alternative MBDs. Results demonstrated that the pleckstrin homology domains of AKT protein kinase and phospholipase C δ1 efficiently directed the assembly and release of virus-like particles (VLPs) from cells expressing chimeric proteins. VLP assembly and release also was mediated in a phorbol ester-dependent fashion by the cysteine-rich binding domain of phosphokinase C γ. Although alternative MBDs promoted VLP assembly and release, the viruses were not infectious. Notably, PrGag processing was reduced, while cleavage of GagPol precursors resulted in the accumulation of Pol-derived intermediates within virions. Our results indicate that the HIV-1 assembly machinery is flexible with regard to its means of membrane association, but that alternative MBDs can interfere with the elaboration of infectious virus cores.